MATERIAL SELECTION OF PROPOSED AIR RECEIVER TANK APPLIED FOR ELECTRICAL GENERATOR - Reza Kamaludin; Rita Sundari; Agus Sudarsono; Rini Anggraini (Universitas Mercu Buana, 2022)
Air receiver tank in electrical generator used as pressured air vessel is mainly consisted of shell cylinder and head part. This work has searched for the more suitable material to be used for the shell and head of the proposed air receiver tank because the older material (SPV 355) has some limitations. This study has been conducted based on several parameters in standard references. The calculations have applied relevant technical formulas such as corrosion factor, thickness design, and Maximum Allowable Working Pressure (MAWP). There are three types of selected materials available that are expected to yield similar previous condition parameters addressing to operational pressure 10 bar and temperature 40oC, i.e., SA-36 (Type I), SA-516 Gr 70 (Type II), and SS-304 (Type III). The economic factor is also taken into consideration. Considering the economic cost and mechanical characteristics, finally the material of Type II is selected to be the most appropriate material to replace SPV 355 material for the proposed air receiver tank. In the upcoming, this study is useful for the knowledge of material design.